2023
DOI: 10.3389/fphar.2023.1113808
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and personalized treatment prediction in lung adenocarcinoma: An in silico and in vitro strategy adopting cuproptosis related lncRNA towards precision oncology

Abstract: Background: There is a rapid increase in lung adenocarcinomas (LUAD), and studies suggest associations between cuproptosis and the occurrence of various types of tumors. However, it remains unclear whether cuproptosis plays a role in LUAD prognosis.Methods: Dataset of the TCGA-LUAD was treated as training cohort, while validation cohort consisted of the merged datasets of the GSE29013, GSE30219, GSE31210, GSE37745, and GSE50081. Ten studied cuproptosis-related genes (CRG) were used to generated CRG clusters an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 86 publications
(131 reference statements)
0
14
0
Order By: Relevance
“…The situation of the target gene in the real world can be described by laboratory data obtained from human samples. The expression level of each mRLncSig lncRNA was investigated by collecting nine pairs of LUAD and adjacent tissues from the clinic 70 . All patients included in this study did not receive any relevant treatment before collecting samples.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The situation of the target gene in the real world can be described by laboratory data obtained from human samples. The expression level of each mRLncSig lncRNA was investigated by collecting nine pairs of LUAD and adjacent tissues from the clinic 70 . All patients included in this study did not receive any relevant treatment before collecting samples.…”
Section: Methodsmentioning
confidence: 99%
“…In both datasets, the drug sensitivity was determined by the area under the dose–response curve (AUC), with lower values indicating greater sensitivity. Our study involves the analysis of drug response data from CTRP and PRISM to identify feasible drug candidates from the high‐scoring group 70 . To do this, we compared drug responses between patients with the highest and lowest decile risk scores and used a threshold of log2FC > 0.1 to screen for drugs with lower AUC in high‐scoring patients 71 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to ferroptosis, cuproptosis isanother key point of RCD research. Furthermore, several cuproptosis-related lncRNA-based signatures have been developed for the prognosis prediction of LUAD patients[34,35].Disul dptosis, differs from the previous RCD such as ferroptosis and cuproptosis, is a novel kind of RCD reported recently opening up new possibilities for cancer treatment. Liu's research revealed that cancer cells overexpressing SLC7A11 undergo a unique form of cell death when exposed to glucose deprivation, distinct from recognized cell death subtypes.…”
mentioning
confidence: 99%